Correction: Author Correction: Tespa1 regulates T cell receptor-induced calcium signals by recruiting inositol 1,4,5-trisphosphate receptors - Jingjing Liang (Nature Portfolio, 2018)
Nature Communications 8: Article number: 15732 (2017); Published: 9 June 2017; Updated: 12 March 2018 In the original version of this Article, the affiliation details for Yan Fang were incorrectly given as “ZJU-UoE Institute, Zhejiang University School of Medicine, Hangzhou 310058, China”. This has now been corrected in both the PDF and HTML versions of the Article.